PERAN MAHKAMAH KONSTITUSI DALAM KONSTITUSIONALITAS HASIL PEMILU - Mochammad Sukedi; Gede Eka Rusdi Antara; Putu Kusuma Dwi Wulandari (Faculty of Law, Mahasaraswati University, Denpasar, 2024)
Independence of the Constitutional Court (MK) in resolving electoral disputes within the context of Indonesia's constitutional democracy. The abstract outlines the constitutional principles governing Indonesia's governance structure, emphasizing the sovereignty of the people and the rule of law. It explores the significance of free and fair elections as a manifestation of democracy, along with the legal framework regulating elections in Indonesia. Furthermore, the abstract examines the jurisdiction of the MK in resolving electoral disputes, highlighting the evolution of the MK in upholding constitutionalism and ensuring democratic processes. The methodological approach used in the research, namely juridical-normative, focusing on legal sources and doctrinal analysis, is also discussed. Overall, the abstract provides a comprehensive overview of the research objectives, methodology, and key findings regarding the role of the MK in safeguarding Indonesia's constitutional democracy.